Agreement between medical students’ peer assessments and faculty assessments in advanced resuscitation skills examinations in South Korea - Jinwoo Jeong; Song Yi Park; Kyung Hoon Sun (Journal of Educational Evaluation for Health Professions, 2021)
Purpose In medical education, peer assessment is considered to be an effective learning strategy. Although several studies have examined agreement between peer and faculty assessments regarding basic life support (BLS), few studies have done so for advanced resuscitation skills (ARS) such as intubation and defibrillation. Therefore, this study aimed to determine the degree of agreement between medical students’ and faculty assessments of ARS examinations. Methods This retrospective explorative study was conducted during the emergency medicine (EM) clinical clerkship of fourth-year medical students from April to July 2020. A faculty assessor (FA) and a peer assessor (PA) assessed each examinee’s resuscitation skills (including BLS, intubation, and defibrillation) using a checklist that consisted of 20 binary items (performed or not performed) and 1 global proficiency rating using a 5-point Likert scale. The prior examinee assessed the next examinee after feedback and training as a PA. All 54 students participated in peer assessment. The assessments of 44 FA/PA pairs were analyzed using the intraclass correlation coefficient (ICC) and Gwet’s first-order agreement coefficient. Results The PA scores were higher than the FA scores (mean±standard deviation, 20.2±2.5 [FA] vs. 22.3±2.4 [PA]; P<0.001). The agreement was poor to moderate for the overall checklist (ICC, 0.55; 95% confidence interval [CI], 0.31 to 0.73; P<0.01), BLS (ICC, 0.19; 95% CI, -0.11 to 0.46; P<0.10), intubation (ICC, 0.51; 95% CI, 0.26 to 0.70; P<0.01), and defibrillation (ICC, 0.49; 95% CI, 0.23 to 0.68; P<0.01). Conclusion Senior medical students showed unreliable agreement in ARS assessments compared to faculty assessments. If a peer assessment is planned in skills education, comprehensive preparation and sufficient assessor training should be provided in advance.